A multi-criteria decision analysis of waste-to-energy technology options in UP Diliman - Abrenica, Kristine Mae N.; Perez, Angela Nicole S.; Diola, Ma. Brida Lea D. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The University of the Philippines-Diliman is 493-hectare land located in Quezon City. Despite having its own materials recovery facility and stud farm, the wastes produced are still not properly utilized. With the growing population of UP Diliman, there is also an increase of waste generation which will need for another solid waste management practice in the university. This paper aims to recommend Waste-to-Energy technology that the campus can use as an addition to its current solid waste management efforts. In this research, past studies were reviewed to quantify and characterize solid wastes in the campus. The university generates 15 metric tons of solid wastes per day with majority of food and yard waste. This information helped in determining four (4) possible Waste-to-Energy technologies namely anaerobic digestion, pyrolysis, biomass gasification, and plasma arc gasification. Criteria which include environmental, sociocultural, technical, and economical were then formulated for evaluation. A total of thirty (30) experts from UP Diliman Academe, DOST, DOE, SWAPP, DENR, QC-EPWMD, and NSWMC were interviewed and asked to answer a survey form. Using Multi-Criteria Decision Analysis particularly Analytic Hierarchy process, the results were analyzed. Anaerobic digestion got the highest rank. Estimated energy output from anaerobic digestion was also computed and found to be 4,943.263 MWh/yr. The estimated amount of methane reduced by anaerobic digestion was also calculated to be 852,672.80 kg in 20 years.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Recycling (Waste, etc.); Waste products as fuel; Multiple criteria decision making